Barbara Fuchs & Emily Weissbourd (eds.), Representing Imperial Rivalry in the Early Modern Mediterranean (Toronto: Toronto University Press, 2015) - Viviana Tagliaferri (Nordicum-Mediterraneum, 2016)
Book review of: Barbara Fuchs, Emily Weissbourd (eds.), Representing Imperial Rivalry in the Early Modern Mediterranean, (Toronto: Toronto University Press, 215), pp. 296, ISBN 9781442619272.